Boosting optimum-path forest clustering through harmony Search and its applications for intrusion detection in computer networks - Costa, Kelton [UNESP]; Pereira, Clayton [UNESP]; Nakamura, Rodrigo [UNESP]; Pereira, Luis [UNESP]; Papa, Joao [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2012)
In this paper we propose a nature-inspired approach that can boost the Optimum-Path Forest (OPF) clustering algorithm by optimizing its parameters in a discrete lattice. The experiments in two public datasets have shown that the proposed algorithm can achieve similar parameters' values compared to the exhaustive search. Although, the proposed technique is faster than the traditional one, being interesting for intrusion detection in large scale traffic networks. © 2012 IEEE.
Keywords: Discrete lattices; Exhaustive search; Harmony search; ITS applications; Optimum-path forests; Traffic networks; Clustering algorithms; Intrusion detection; Social networking (online); Forestry; Algorithms